2017
DOI: 10.21608/jfds.2017.37107
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation of Cupcake Treated with Hawthorn Leaves on Diabetic Rats

Abstract: The aim of this study was to produce cupcake by replacement of 10, 20% wheat flour (WF) with hawthorn leaves(Crataegus sp.) powder (HLP). The effect of this replacement on the chemical, organoleptic, stability during storage cupcake for 14 day was investigated. Biological assay was also conducted on diabetic male rats. The results indicated that there were no clear differences between (WF) and (HLP) especially in moisture content and crude protein. However, (HLP) had higher contentes of ash, crude fat and crud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…These results confirm those that were reported previously [53], which showed that yogurt supplemented with Cinnamon herb extract had a more undesirable flavor profile overall compared to plain yogurt. Furthermore, a previous study [54] found that the addition of Hawthorn leaf powder reduced the organoleptic properties of cupcakes. In addition, another study [55] found that adding olive leaf extract at the concentrations of 0.2 and 0.4% had an unfavorable effect on the organoleptic properties of yogurt samples.…”
Section: Chemical Compositions Physicochemical and Sensory Characteri...mentioning
confidence: 93%
“…These results confirm those that were reported previously [53], which showed that yogurt supplemented with Cinnamon herb extract had a more undesirable flavor profile overall compared to plain yogurt. Furthermore, a previous study [54] found that the addition of Hawthorn leaf powder reduced the organoleptic properties of cupcakes. In addition, another study [55] found that adding olive leaf extract at the concentrations of 0.2 and 0.4% had an unfavorable effect on the organoleptic properties of yogurt samples.…”
Section: Chemical Compositions Physicochemical and Sensory Characteri...mentioning
confidence: 93%